2011
DOI: 10.1007/s11105-010-0284-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Fatty Acid Desaturases in Soybean (Glycine max)

Abstract: Fatty acid desaturases can introduce double bonds into the hydrocarbon chains of fatty acids to produce unsaturated fatty acids. In the present study, 29 full-length desaturase genes were identified from soybean genome by a thorough annotation exercise. A comprehensive analysis was performed to characterize phylogeny, chromosomal locations, structures, conserved motifs, and expression patterns of those genes. The soybean genes were phylogenetically clustered into nine subfamilies with the Arabidopsis counterpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
92
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 44 publications
18
92
1
Order By: Relevance
“…In soybean, one trait is often controlled by several homologous genes, and this presents a major challenge for breeding soybean lines with multiple traits (Chi et al 2011;Schmutz et al 2010). Initiated by USDA-ARS in 1952, traditional breeding has been successful in identifying loci responsible for oleic acid and linolenic acid contents, but selection was primarily based on phenotype because of limited knowledge about the genes and molecular markers associated with the trait (Fehr 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In soybean, one trait is often controlled by several homologous genes, and this presents a major challenge for breeding soybean lines with multiple traits (Chi et al 2011;Schmutz et al 2010). Initiated by USDA-ARS in 1952, traditional breeding has been successful in identifying loci responsible for oleic acid and linolenic acid contents, but selection was primarily based on phenotype because of limited knowledge about the genes and molecular markers associated with the trait (Fehr 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The source of dethiobiotin in alga may result from an important and unsuspected symbiosis with bacteria. The source of cobalamin seems to be bacteria, indicating an important and unsuspected symbiosis (Croft et al 2005). The importance of biotin in the symbiotic interactions between the alga and the fungus in Peltigera was discussed (Bednar and Holm-Hansen 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Biotin is also called vitamin H or vitamin B 7 and is a cofactor responsible for carbon dioxide transfer in several carboxylase enzymes, which play significant role in various metabolic reactions such as fatty acid synthesis, branched chain amino acid catabolism, and gluconeogenesis (De Clercq 1997;Zempleni and Mock 1999). For example, acetyl-CoA carboxylase (ACCase) catalyzes the biotin-dependent carboxylation of acetyl-CoA to produce malonyl-CoA, which is the essential first step of the biosynthesis of long chain fatty acids (Chi et al 2011;Li et al 2010;Gu et al 2011;Stolf-Moreira et al 2011). Besides, biotin plays a role in the citric acid cycle, which is the process by which biochemical energy is generated during aerobic respiration (De Clercq 1997;Zhang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this pathway, delta-12 desaturase, encoded by the fatty acid desaturase-2 (FAD2) gene, primarily converts oleic acid (18:1) to linoleic acid (18:2) in storage lipids in seeds by introducing a double bond at the 12th carbon in the fatty acid hydrocarbon chain (Mikkilineni and Rocheford, 2003). Since the first plant FAD2 gene was cloned in Arabidopsis thaliana (Okuley et al, 1994), several FAD2 genes have been identified, isolated, and characterized from other plant species, such as maize (Mikkilineni and Rocheford, 2003;Beló et al, 2008), safflower (Guan et al, 2012;Cao et al, 2013), Camelina sativa (Hutcheon et al, 2010), soybean (Pham et al, 2010;Chi et al, 2011), Brassica napus Yang et al, 2012), peanut (Jung et al, 2000;Lopez et al, 2000), flax (Krasowska et al, 2007), sunflower (Rolletschek et al, 2007), and olive (Georgios et al, 2005). Only a single copy of FAD2 was identified in Arabidopsis and maize (Okuley et al, 1994;Beló et al, 2008), while multiple copies of FAD2 were found in soybean (Li et al, 2007;Schlueter et al, 2007), maize (Mikkilineni and Rocheford, 2003), cotton (Zhang et al, 2009), and safflower (Cao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%